Basic dynamics of extortion racketeering (2016)
The emergence and prevalence of systemic extortion depends on particular institutional arrangements, produced as adaptive responses of the interaction between different social actors. The following typology characterises these arrangements in six categories, involving three main social actors: criminal organisations, state and civil society. While the six categories focus on institutional arrangements that foster systemic extortion, the typology could be loosely described as presenting two categories focusing on each of the three main social actors. The predominant social actor in each category derives from the relative importance of that actor for the specific aspect of the institutional arrangements addressed by each category. The major contribution of this typology is the acknowledgement that extortion rackets cannot be understood without looking at the dimensions of the political environment they exist in (i.e. state) and the social environment (i.e. civil society, which comprises potential and actual victims). Following the six categories, the main factors allowing for the emergence and persistence of systemic extortion are grouped into socio-spatial, socio-normative and socio-cognitive factors.